2017
DOI: 10.5536/kjps.2017.44.4.259
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Early Chick Weight on Market-Weight in Korean Native Chickens

Abstract: This study was to investigate the effect of chick weight in the early growth period on market-weight of Korean native chickens (KNCs). We measured the body weights of 1,087 chickens (male 479, female 608) of 13 KNC strains at 1-84 days of age at two week intervals. The growth performance of the 13 KNC strains was investigated. Correlation coefficients among the weights of chickens in each growth period and regression of market-weight on early chick weights were analyzed. The results showed that the average bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
2
0
1
Order By: Relevance
“…The BW and ADG of male Thai native chickens was higher than that of female Thai native chickens, consistent with several previous studies, such as [39][40][41]. However, when considering the average BW between Thai native chickens in this study and other Thai native chicken breeds, it was found that Thai native chickens in this study had a significantly higher BW, as in Lueng Hang Kao Kabinburi [42] in Chee [43].…”
Section: Discussionsupporting
confidence: 90%
“…The BW and ADG of male Thai native chickens was higher than that of female Thai native chickens, consistent with several previous studies, such as [39][40][41]. However, when considering the average BW between Thai native chickens in this study and other Thai native chicken breeds, it was found that Thai native chickens in this study had a significantly higher BW, as in Lueng Hang Kao Kabinburi [42] in Chee [43].…”
Section: Discussionsupporting
confidence: 90%
“…Currently, KNCs have been shipped to the market at age 10 weeks; therefore, it is important to develop an efficient breeding strategy that can ensure that individuals with good growth capability can be selected in advance before reaching market-weight. The related research to determine the age at which to select birds for breeding programs showed that BW at age 8 weeks had the highest correlation among early growth periods with market-weight [13]. Moreover, BW at age 8 weeks was significantly positively correlated not only to market weight but also to BW at age 20 weeks; thus, it is considered the best representation of the overall growth of KNCs.…”
Section: Animals and Phenotypesmentioning
confidence: 99%
“…Previous studies by Tongsiri et al [ 14 ] revealed that it takes 14–16 weeks for Thai native chickens to reach an average body weight of 1.2–1.5 kg, which is the market weight. Moreover, Korean native chickens take ten weeks to reach approximately 2.0 kg [ 15 ] while East African chickens take 19–21 weeks [ 1 ]. The different management in each area [ 16 , 17 ] and shortage of good genetic animals for the next generation is another major obstacle for farmers…”
Section: Introductionmentioning
confidence: 99%